Commutativity Results for Multiplicative (Generalized) (α,β) Reverse Derivations on Prime Rings - Alhaidary, Zahraa S. M.; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2021)
Let be a prime ring, be a non-zero ideal of and be automorphism on. A mapping is called a multiplicative (generalized) reverse derivation if where is any map (not necessarily additive). In this paper, we proved the commutativity of a prime ring R admitting a multiplicative (generalized) reverse derivation satisfying any one of the properties: for all x, y